Enhancing nursing competency through virtual reality simulation among nursing students: a systematic review and meta-analysis - Cho, Mi-Kyoung; Kim, Mi Young (Frontiers in Medicine, 2024)
Studies on the effectiveness of virtual reality (VR) in nursing education have Aim(s): Studies on the effectiveness of virtual reality (VR) in nursing education have explored its impact on learning outcomes, emotional immersion and engagement, learner explored its impact on learning outcomes, emotional immersion and engagement, learner self-confidence, and satisfaction, generally showing positive aspects. However, there is a self-confidence, and satisfaction, generally showing positive aspects. However, there is a need for a systematic review to examine the specific influence of VR-based education on need for a systematic review to examine the specific influence of VR-based education on nursing students' practical competency. nursing students' practical competency.According to the PRISMA 2020 guidelines, 22 studies were selected based on Method(s):